Avaliação de compostos bioativos de coprodutos do processamento de acerola e goiaba fermentados com isolados de lactobacillus potencialmente probióticos - Oliveira, Sabrina Duarte de (2020)
Brazil is the third-largest fruit producer in the world and a large part of this production is destined to the food processing industry, generating a expressive amount of agro-industrial coproducts, which are generally discarded. These coproducts are naturally sources of bioactive compounds, in addition, some mechanisms can stimulate the production of these compounds in this matrix, as is the case of fermentation by pre-selected microorganisms, such as lactic acid bactéria (LAB). Thus, the objective of this study was to carry out the inoculated fermentation (Lactobacillus plantarum 53, L. paracasei 106, L. casei L-26, and L. fermentum 56, in co-culture in a ratio of 1:1:1:1) of acerola coproducts (Malpighia emarginata D.C., ACE) and guava (Psidium guajava L., GUA) at a temperature of 37 °C, at 200 rpm, for 120 hours, evaluating the change in the profile of bioactive compounds during fermentation. Before fermentation, analyzes of physical-chemical characterization of the coproducts of acerola and guava were realized. In the intervals of zero, 8, 24, 48, 72 and 120 hours of fermentation viable cell count of probiotic Lactobacillus was performed. Physical-chemical parameters, the contents of bioactive compounds (phenolic and total phenolic profiles, total carotenoids, flavonoids and vitamin C) and antioxidant activity (FRAP and ABTS) were evaluated at zero, 48, 72 and 120 hours of fermentation. At zero fermentation time, the viable cell count of probiotic Lactobacillus for ACE and GUA was greater than 8.5 log CFU mL-1 and after 120 hours of fermentation it fell (p ≤ 0.05) to values ≥5.0 log CFU/ml. As for the colorimetry parameters, there was an increase in luminosity and a reduction in contrast throughout the fermentation, and the fermented coproducts tended to go from red to yellow-red during this period (p ≤ 0.05). There was a decrease in the content of total soluble solids during fermentation, with a concomitant increase in titratable acidity and lactic acid content, and reduction in pH, for both fermented coproducts (p ≤ 0.05). The ascorbic acid content decreased for ACE and increased for GUA during fermentation (p≤0.05). Different phenolic compounds were found in ACE and GUA during fermentation. The content of flavonoids and total phenolics in the fermented by-products increased during the fermentation and possibly favored the greater antioxidant activity observed, mainly for ACE (p≤0,05), this was confirmed in the Principal Component Analysis, which showed a strong correlation of these compounds with the activity antioxidant observed in the FRAP and ABTS assays. The results obtained in this study indicate that the fermentation of ACE and GUA coproducts, when inoculated with strains of Lactobacillus in co-culture (L. plantarum 53, L. paracasei 106, L. casei L-26 and L. fermentum 56), it can be a strategy to improve its contents of bioactive compounds and antioxidant activities, and, consequently, potential health properties.